Temporal dynamics of the friendship paradox in a smartphone communication network - Cheng Wang; Omar Lizardo; David S. Hachen (Applied Network Science)
Abstract The friendship paradox, initially discussed by Scott Feld in 1991, highlights a counterintuitive social phenomenon where individuals tend to have fewer friends than their friends do on average. The sociological implications of this paradox are profound, as it can create a distorted understanding of social norms and consequently influence beliefs, attitudes, and behaviors, particularly when highly connected individuals present a skewed representation of those norms. In essence, it can lead individuals to misjudge what is typical or desirable within their social circles. This study investigates the temporal dynamics of the friendship paradox using smartphone communication data from over 600 incoming freshmen at the University of Notre Dame participating in the NetHealth project. By tracking the friendship index– the ratio of an individual’s friends’ average number of friends to their own number of friends– over 119 days during the Fall semester of 2015, we examine how the paradox evolves over time. Our findings reveal that the friendship index stabilizes more rapidly than both the individuals’ own degree and the variation among their friends’ degrees. Results from the latent growth-curve model (LGCM) confirm that while the friendship index continues to increase, its growth rate declines over time. Moreover, the LGCM identifies individual degrees, ethnic backgrounds, and personality traits as influential factors shaping the manifestation and development of the friendship paradox. By exploring the mechanisms underlying this paradox in a dynamic communication network, this study enhances our understanding of the structural factors influencing the evolution of the friendship paradox in digitally mediated interactions.